Digitalization of Android-Based Services Searching Using the Human-Centered Design Approach - Djusmin, Vicky Bin; Yasir, Fajar Novriansyah (Program Studi Teknik Elektro Universitas Khairun, 2024)
Using applications is considered an effective solution in providing services to user needs. The current way to order services is to ask relatives or use social media as information channels. For this reason, an integrated service digitalization application is needed in one application to make it easier for users to find and select the services required. Service providers also have the media to promote their services so that they stand on service marketing increases. The methodology in this study is descriptive qualitative with the human-centered design (HCD) approach, which includes inspiration, ideation, and implementation. The data collection process is done by interviewing and focus group discussion. The system development model uses a prototype model. The results showed that the application's design meets the HCD criteria by making feedback from the user a significant guide in building a system regarding features, functionality, and user interface. Stages in system development have been carried out to obtain a comprehensive picture of system development. Application test results using the Blackbox type show that the applications can run according to their respective functionality.